Неметалеві включення у великому ковальському злитку зі сталі 25ХНЗМФА - Нарівський, А.В.; Смірнов, О.М.; Тарасевич, М.І.; Кондратюк, С.Є.; Перехода, В.В. (Physico-technological Institute of Metals and Alloys, 2023)
For the power and heavy engineering industries the unique and overall products from steel, made from large (to 600 ton) forging ingots, are needed. At a solidification in large ingots the chemical and physical heterogeneities, growing sizes and unevenness of distribution in steel of non-metallic inclusions (NMIs) are intensively formed, and operating descriptions of finish goods reduce considerably. The content and distribution of NMIs in an ingot depends from the processes of melting, deoxidization and modification of steel, the terms of the casting and crystallization of metal. At heightened maintenance of gases in steel this inclusions can be concentrated on the boundary “metal – gas cavity”. Dangerous for properties of the steel products are the fusible inclusions of oxysulphides which are released during crystallization of ingot. Such inclusions reduce durability of intergrain connections, especially at high temperatures (red brittness). A large danger is presented also by the refractory inclusions that melt at temperature higher, than the temperature of liquid steel. These inclusions have sharp faces and create the concentrations of stress in a solid metal which there are by the sources of beginning of processes of his destruction. The inclusions that have a compact (spherical) form are less harmful for properties of steel. Such inclusions are forming in ingots in that case, when the temperature of their melting is not high of a melt and they badly moisten by a metal. Besides to the considered non-metallic inclusions, oxides, sulfides, silicates, sulfusilicates, alumosilicates et al can also appear in ingots. The content, dispersion and composition of non-metallic inclusions formed in the 142-ton ingot, which was cast in vacuum from 25ХНЗМФА steel, were researched.